2020
DOI: 10.1093/pubmed/fdaa195
|View full text |Cite
|
Sign up to set email alerts
|

The experience of the health care workers of a severely hit SARS-CoV-2 referral Hospital in Italy: incidence, clinical course and modifiable risk factors for COVID-19 infection

Abstract: Background During the COVID-19 pandemic, the health care workers (HCWs) at the frontline have been largely exposed to infected patients, running a high risk of being infected by the SARS-CoV-2 virus. Since limiting transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in health care setting is crucial to avoid the community spread of SARS-CoV-2, we want to share our experience as an early hit hospital where standard infection control practices have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 38 publications
(38 reference statements)
7
39
5
1
Order By: Relevance
“…Similar to prior report updates, estimates did not indicate an association between sex (13 studies [ 3–6 , 9 , 11–13 , 15 , 17–20 ]) or age (12 studies [ 3–5 , 9 , 11–13 , 15 , 17–20 ]) and risk for SARS-CoV-2 infection or seropositivity. Fifteen new studies found no consistent association between health worker role (nurse vs. physician) and risk for SARS-CoV-2 infection ( 3–5 , 7–12 , 14–16 , 18–20 ).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Similar to prior report updates, estimates did not indicate an association between sex (13 studies [ 3–6 , 9 , 11–13 , 15 , 17–20 ]) or age (12 studies [ 3–5 , 9 , 11–13 , 15 , 17–20 ]) and risk for SARS-CoV-2 infection or seropositivity. Fifteen new studies found no consistent association between health worker role (nurse vs. physician) and risk for SARS-CoV-2 infection ( 3–5 , 7–12 , 14–16 , 18–20 ).…”
supporting
confidence: 54%
“…For this update, 12 cohort studies ( 3–9 , 11 , 14 , 15 , 18 , 19 ) and 6 cross-sectional studies ( 10 , 12 , 13 , 16 , 17 , 20 ) were added ( Supplement Table 1 ). Four studies were done in the United States ( 4 , 7 , 18 , 20 ), 10 in Europe (Spain [ 5 , 11 , 14 ], Italy [ 8 , 9 ], the United Kingdom [ 12 , 17 ], France [ 13 ], Sweden [ 15 ], and the Netherlands [ 15 ]), 2 in India ( 6 , 10 ), and 1 each in China ( 19 ) and Egypt ( 3 ). As with studies included in prior updates, the studies had methodological limitations, including potential recall bias, low or unclear participation rates, small sample sizes, and potential collinearity.…”
mentioning
confidence: 99%
“…For this reason, we investigated HCWs’ level of information and perceptions of the prevention and control of the COVID-19 pandemic. It is crucial for HCWs to be prepared and to apply all IPC in facing COVID-19 [ 29 , 30 , 31 ] considering that the prevalence of the infection among HCWs exceeded 10% in Italy [ 32 , 33 , 34 ] with a consequent loss of capacity for hospitals to respond adequately to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial for HCWs to be prepared and to apply all IPC in facing COVID-19 [29][30][31] considering that the prevalence of the infection among HCWs exceeded 10% in Italy [32][33][34] with a consequent loss of capacity for hospitals to respond adequately to pandemic.…”
Section: Discussionmentioning
confidence: 99%